IMPLEMENTASI PENGUATAN HUBUNGAN NASABAH DAN MANAJEMEN RISIKO DI PT AGRODANA FUTURES - Susanto, Tsabita Cendikia; Supriyono, Supriyono (STKIP Pesisir Selatan, 2025)
Futures trading is a financial instrument that offers high profit potential but also carries significant risks, such as price fluctuations, leverage, and market volatility. This study aims to analyze how Customer Relationship Management (CRM) and risk management are applied in futures marketing activities. The focus of the research is on the role of an Account Executive in building relationships with clients and guiding them to understand trading risks. The study employs a qualitative descriptive approach, with Account Executives at PT Agrodana Futures as the research subjects. Data were collected through in-depth interviews, direct observation, and literature review as supporting data. The findings indicate that Account Executives play an active role in delivering market information, assisting clients in using stop loss features as a risk management tool, and ensuring that clients understand transaction risks. The impact of the study shows that the integration of CRM and risk management enhances client satisfaction and loyalty. The innovation of this research lies in providing a comprehensive understanding of how Account Executives simultaneously implement client relationship strategies and risk management practices, enabling more responsible futures trading.